The prevalence of Cytomegalovirus (CMV) infection among infants and correlation between CMV PCR with clinical outcomes in a tertiary teaching hospital in Malaysia - Norjihan Abdul Hamid,; Nabilah Awang,; Alwi Muhd Besari @ Hashim,; Suharni Mohamad,; Zeti Norfidiyati Salmuna, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Congenital cytomegalovirus (cCMV) infection is the leading infectious cause of congenital hearing loss and neurodevelopmental disability. This study aimed to describe the prevalence and clinical manifestations of infants age 12 months and below with CMV infection in Hospital Universiti Sains Malaysia (Hospital USM) and to determine the correlation between CMV PCR with clinical outcomes. A total of 648 hospitalized infants with clinically suspected cases of cytomegalovirus infection admitted to Hospital USM from January 2018 to December 2018 were tested for anti-CMV IgM and IgG by electrochemiluminescence immunoassay method. The results suggestive of CMV infection were requested for the second serum sample at 2-4 weeks’ interval together with plasma samples for CMV DNA viral load quantification by real-time PCR and maternal sample for serological analysis. Correlation of CMV viral load with clinical outcomes was analyzed using the point- biserial correlation. The results showed that the prevalence of acute CMV infection was 6.48 % (42/648) and cCMV infection was 0.3% (n=2/648). The findings were as follows: acute CMV infection (n = 42), passive immunity (n = 113) and inconclusive (n =41).) CMV hepatitis (p-value= 0.018), rash (p-value= 0.043), presumed sepsis (p-value=0.044) and abnormal hearing (p-value 0.031) were significantly associated with CMV status. Significant moderate correlation between CMV viral load and abnormal hearing assessment was observed. As a conclusion, CMV hepatitis, presumed sepsis, rash, and abnormal hearing were associated with the infant’s CMV status. A significant correlation was found between CMV viral load and abnormal hearing.